Effect of micro alloying of steel with niobium on the mechanical properties of heat-strengthened rebar - A. I. Posti (Литьë и металлургия)
One of the most effective micro-alloying elements in the production of class 500 fittings is vanadium. However, the production technology is multi-stage and expensive, so the use of ferrovanadium makes the production of vanadium-containing fittings for mass use unprofitable. In this regard, it is necessary to reduce the cost of finished products by replacing ferrovanadium with ferroniobium while preserving all the mechanical, physical and operational characteristics of the metal.Objective: to determine the effect of the quantitative content of niobium in steel in the production of hot-rolled rebar S-500WC in coils at the mill 370/150 of OJSC “BSW – Management Company of the Holding “BMK” in accordance with the requirements of the Israeli standard SI 4466-3:2013 at various temperature and speed parameters of rolled products. The normalized mechanical properties of s-500WC reinforcing steel of all profiles (No. 8–16) in accordance with THE requirements of si 4466-3:2013 are: yield strength – 500–650 MPa, ductility – 1.15–1.35, elongation of – at least 11 % and total elongation at break of – at least 7.5 %.